2011
DOI: 10.1007/s13524-011-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Out of Sight, Out of Mind: Including Group Quarters Residents With Household Residents Can Change What We Know About Working-Age People With Disabilities

Abstract: A d v a n c i n g t h e W o r l d o f W o r kM A Y 2 0 0 9 iii ABSTRACTInformation about residents of institutional and noninstitutional group quarters (GQ),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…If the rate of institutionalization changed substantially over the study period, it could bias our estimation of changes over time. Fortunately this does not appear to be the case because the changes in institutionalization due to disability have been modest and the proportion of the target population at ages 45–64 in institutions is low (She and Stapleton 2006, Stapleton, Honeycutt and Schechter 2012). An additional limitation pertains to the cross-sectional nature of the data, which precludes examining causal effects of the hypothesized precursors.…”
Section: Discussionmentioning
confidence: 99%
“…If the rate of institutionalization changed substantially over the study period, it could bias our estimation of changes over time. Fortunately this does not appear to be the case because the changes in institutionalization due to disability have been modest and the proportion of the target population at ages 45–64 in institutions is low (She and Stapleton 2006, Stapleton, Honeycutt and Schechter 2012). An additional limitation pertains to the cross-sectional nature of the data, which precludes examining causal effects of the hypothesized precursors.…”
Section: Discussionmentioning
confidence: 99%
“…We use the integrated public use microdata files (Ruggles et al, 2010) of the ACS, pooled across 2009 to 2011 to ensure adequate sample sizes by type of disability and demographic characteristics. We exclude individuals living in group quarters because research has found this population to be systematically different from the population of people with disabilities living in the community (Stapleton, Honeycutt, & Schechter, 2012). We also limit our analysis to individuals aged 25 to 64 years to focus on the working-age population.…”
Section: Methodsmentioning
confidence: 99%
“…When employment services are provided, they are most often provided as “late interventions.” SSA, for example, focuses its employment support efforts on its existing DI and SSI beneficiaries, with very limited success in moving beneficiaries back to work (Liu & Stapleton, 2011). Other research has suggested that few people with disabilities without jobs are actively looking for work (Erickson & Lee, 2008) and that only a small number participate in public vocational rehabilitation services that are designed to increase participation in the labor market (Stapleton, Honeycutt, & Schechter, 2008).…”
Section: Literature Review and Overview Of Programsmentioning
confidence: 99%